The new findings from Antikythera mechanism front plate astronomical dial and its reconstruction - Aristeidis Voulgaris (mediaGEO soc. coop., 2019)
The present study aims to investigate the astronomical calendar-dial display of the Antikythera Mechanism Front Plate. The design, position and role of the Zodiac ring, are investigated and discussed. Special photographs taken from the ancient prototype, give us new information about the design and operation of the front dial. From these new findings about the Zodiac ring, we conclude that the user of the mechanism was able to easily perform astronomical calculations at any selected time - of past or future date. Based on the new findings during ‘'The Functional Reconstruction of Antikythera Mechanism Project'' (FRAMe), we reconstructed the new bronze front plate and we placed it in our functional model of the Antikythera Mechanism.